Research on Transmission Characteristic of ZF 9-speed Automatic Transmission - Junyan Wang; Junyu Cai; Xin Fan (Jixie chuandong)
Taking the ZF 9-speed automatic transmission (9HP48) as the research object，the power transmission line in each gear of the automatic transmission is clarified. The transmission ratio and torque ratio (considering friction loss) of each gear are theoretically derived. The М.А.Крейнeс formula is used to calculate the transmission efficiency of 9 forward gears and 1 reverse gear. To verify the theoretical derivation，AMESim simulation software is used for building the simulation model of the automatic transmission. The transmission ratio and transmission efficiency values of each gear are obtained through the simulation calculation. The simulation results are consistent with the theoretical analysis results. The simulation results verify the correctness of the theoretical derivation and provide a basis for optimizing the automatic transmission scheme in the future.